2023
DOI: 10.3390/jcm12185800
|View full text |Cite
|
Sign up to set email alerts
|

Vegan Diet in Dermatology: A Review

Hannah Lee,
Nathan Sim,
Audrey Fotouhi
et al.

Abstract: Diet is known to play a role in the development of skin disorders. While a vegan diet is frequently described as a risk factor for skin disease secondary to nutritional deficiency, this risk may be overestimated. This review aims to debunk myths and provide information on skin disorders and inflammatory skin conditions that have associations with specific nutritional deficiencies in the context of a vegan diet. A literature search was performed for each nutrient and inflammatory skin disease using the PubMed/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…These include low-energy, vegan, and vegetarian diets, as well as weight loss programs incorporating modified dietary strategies. Additionally, gluten-free, Mediterranean, and very-low-calorie diets devoid of carbohydrates have shown promise in supporting individuals with psoriasis [15]. Furthermore, the results of the meta-analysis studies demonstrated a significant association between obesity and vitamin D levels, with an increased prevalence of vitamin D deficiency among obese and overweight populations (defined by BMI index) in comparison to lean subjects, irrespective of age or ethnicity [16].…”
Section: Introductionmentioning
confidence: 98%
“…These include low-energy, vegan, and vegetarian diets, as well as weight loss programs incorporating modified dietary strategies. Additionally, gluten-free, Mediterranean, and very-low-calorie diets devoid of carbohydrates have shown promise in supporting individuals with psoriasis [15]. Furthermore, the results of the meta-analysis studies demonstrated a significant association between obesity and vitamin D levels, with an increased prevalence of vitamin D deficiency among obese and overweight populations (defined by BMI index) in comparison to lean subjects, irrespective of age or ethnicity [16].…”
Section: Introductionmentioning
confidence: 98%